Effects of rhythmic visual cues on cognitive resources allocation characterized by electroencephalographic (EEG) features during human gait initiation. (14th May 2021) - Zhou, Huilin; Shi, Changcheng; Xu, Jialin; Ma, Yehao; Wang, Yu; Lian, Shidong; Yang, Jian; Zuo, Guokun
Highlights: CNV during GI preparation was analyzed to represent cognitive resources allocation. More negative CNV amplitude under non-rhythmic visual cues during GI preparation. Lower cognitive resource demands during GI preparation under rhythmic condition. Abstract: Rhythmic visual cues are beneficial in gait initiation (GI) in Parkinson's disease patients with freezing of gait (FOG), however, the underlying neurophysiological mechanism remains poorly understood. The cognitive control modulated by visual cues during GI has been investigated and considered as a potential factor influencing automatic motor actions, but it is unclear how rhythmic visual cues affect cognitive resources demands during GI. The purpose of this study was to explore the effect of rhythmic visual cues on cognitive resources allocation by recording the anticipatory cerebral cortex electroencephalographic (EEG) activity during GI. Twenty healthy participants initiated gait in response to the rhythmic and non-rhythmic visual cues of stimulus presentation. We assessed the contingent negative variation (CNV) of averaged EEG data over 32 electrode positions during GI preparation, the results of which showed that the CNV was induced over prefrontal, frontal, central, and parietal regions in both rhythmic conditions and non-rhythmic conditions. Overall, different visual cues modulated the amplitude of CNV in the early and late stages of the GI preparation. Compared with the non-rhythmic condition, the CNV amplitude was lower in rhythmic condition over displayed regions precede the GI onset. In the late stage of GI preparation, it showed significant differences between the two conditions in prefrontal, frontal, and central regions, and the amplitude of CNV was lower under rhythmic condition. More to the point, the differences were more obvious in the late stage of GI preparation between the two conditions, which was closely associated with the cognitive resources. Therefore, the results indicate that less cognitive resources allocation is required to trigger GI under rhythmic visual cues compared with non-rhythmic visual cues. This study may provide a new insight into why rhythmic visual cues are more effective in improving GI ability compared to non-rhythmic visual cues.